"Protected" marine shelled molluscs: thriving in Greek seafood restaurants - KATSANEVAKIS, S.; POURSANIDIS, D.; ISSARIS, Y.; PANOU, A.; PETZA, D.; VASSILOPOULOU, V.; CHALDAIOU, I.; SINI, M. (Mediterranean Marine Science, 2011)
International agreements as well as European and national legislation prohibit exploitation and trading of a number of edible marine shelled molluscs, due to either significant declines in their populations or destructive fishing practices. However, enforcement of existing legislation in Greece is ineffective and many populations of “protected” species continue to decline, mainly due to poaching. The extent of illegal trading of protected bivalves and gastropods in Greek seafood restaurants was investigated by interviewing owners or managers of 219 such restaurants in 92 localities. Interviews were based on questionnaires regarding the frequency of availability in the menus and the origin of twenty-one species or groups of species, among which eight are protected - illegally exploited. Forty-two percent of the surveyed restaurants were found to serve at least one of the protected ¬- illegally exploited species. Among the illegally traded species, Lithophaga lithophaga, Pecten jacobaeus, and Pinnanobilis were served in a relatively high proportion of the surveyed restaurants (22.8%, 19.2%, and 16.4% respectively), outrunning many commercial species. In many cases these species were always or often available (11.4%, 4.6% and 5.0% respectively). There was substantial spatial variation in the proportion of restaurants that illegally served protected species with differing patterns for each species; very high proportions of illegal trading were observed in some marine regions (e.g., date mussels were served in >65% of the seafood restaurants along the coastline of Evvoikos Gulf). In most cases the illegally traded species were of local origin, while there was no finding of illegally imported molluscs from other countries. The strategy for enforcement of existing legislation should be greatly improved otherwise protection of shelled molluscs will remain ineffective.